Structural position of Tolmachevsky active magmatic center in Southern Kamchatka and its origin - A. G Nurmukhamedov; M. D. Sidorov (Georesursy)
This paper gives an overview of the results of deep geological and geophysical studies carried out in the south of Kamchatka and in the adjacent Pacific Ocean. The description of the volumetric density model and its analysis in conjunction with other data are presented herein. The data regarding the Tolmachevsky active magmatic center (TAMC) structural position and its origin is supplemented. The investigations allow to identify a closed-boundary mantle protrusion which has been formed in the Nachikinskaya transverse dislocation zone (Nachikinskaya TDZ) no later than the Early Miocene. The dimensions of the major and minor axes of the protrusion are 123 and 84 km, respectively. Localised areas of deconsolidation associated with melting chambers are identified in the lower part of the mantle protrusion at a depth of 35-45 km. The formation of the protrusion may be attributed to the pushing of magma of ultrabasic composition from the upper mantle and its subsequent intrusion into the lower layers of the Earth's crust. The intrusion takes place along the weakened zone formed at the initial stage of shear dislocation that has happened in the Miocene-Pliocene period. The differentiation of magma entering the Earth's crust from melting chambers as well as heat flows from the same sources form areas of focal melting and, as a consequence, lead to the formation of an intrusive massif of moderately medium acidic composition. Periodic magma advancement along the weakened zone in the TAMC area is accompanied by a series of weak earthquakes. The TAMC is genetically related to the mantle protrusion and forms an integral part of it.The subducting oceanic lithosphere inflection zones are the areas of tectonic stress accumulation and its periodic release in the form of earthquakes. The highest density of seismic events with a magnitude M ≥ 5 is observed in the seismic lineament located closest to the coastline in the zone of maximum slab inflection in the depth interval of 30-50 km.